ANALISIS ASESMEN DIAGNOSTIK NON KOGNITIF DALAM MENINGKATKAN KUALITAS PEMBELAJARAN PAI DI KELAS 4 SDN 1 ULU LAPAO-PAO - Nia Angraeni; Muhammad Akbar; Nurhayat (Jurnal Teknologi Pendidikan Madrasah, 2025)
Islamic Religious Education learning in grade 4 of SDN 1 Ulu Lapao-pao is still focused on cognitive aspects such as memorizing material and understanding texts without paying full attention to non-cognitive aspects such as attitudes, morality and interpersonal skills. The implementation of the independent curriculum has not fully mastered the contents of the learning tools including the scope of its assessment so that the application of non-cognitive diagnostic assessments in the Islamic Religious Education learning process is not optimal. This is an obstacle in knowing the development and needs of students as a whole. The formulation of the problem in this study is how to analyze non-cognitive diagnostic assessments in improving the quality of Islamic Religious Education learning in grade 4 of SDN 1 Ulu Lapao-pao. The purpose of the study was to determine how non-cognitive diagnostic assessments improve the quality of Islamic Religious Education learning in grade 4 of SDN 1 Ulu Lapao-pao. The research method used is qualitative, phenomenological research type; the object of research is the procedure for the non-cognitive diagnostic assessment process and the quality of Islamic Religious Education learning in grade 4 of SDN 1 Ulu Lapao-pao; the research procedures used include observation, interviews, and documentation; research instruments in the form of observation sheets for teachers and students; data analysis techniques in the form of data collection, data reduction, data presentation, drawing conclusions, and assessing student learning outcomes. The results of the study showed that with the analysis of non-cognitive diagnostic assessments, especially in the analysis of student learning conditions and styles, it showed that most students at SDN 1 Ulu Lapao-pao were very ready to follow the teaching and learning process of Islamic Religious Education. While the observation of learning styles showed that most students in grade 4 had an audio learning style. This is what then became a reference for teachers in creating Islamic Religious Education learning designs which can then improve the quality of Islamic Religious Education learning at the school.